2000
DOI: 10.1034/j.1399-3003.2000.16f07.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prelung transplant clinical status on post-transplant survival of children with cystic fibrosis

Abstract: The aim of this study was to determine whether transplanting paediatric cystic fibrosis (CF) patients later in the course of their disease was detrimental to their post‐transplant survival. Data was collected from 51 children with CF undergoing lung or heart‐lung transplantation May 1988–March 1999. The following risk factors were tested by Cox proportional hazards modelling: age at transplant; sex; donor/recipient sex mismatch; donor/recipient cytomegalovirus (CMV) mismatch; cold and warm graft ischaemic time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In some centers, patients with CF specifically and ventilator-dependent respiratory failure are not considered appropriate candidates for transplant due to concerns that they will not receive their organs in time and that the possibility of transplantation will compromise appropriate terminal care. 15 Patients listed for lung transplantation are often removed from the transplant waiting list when they enter a terminal phase. 16 In other centers, lung transplantation is routinely practiced for patients with CF reaching respiratory failure and requiring mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In some centers, patients with CF specifically and ventilator-dependent respiratory failure are not considered appropriate candidates for transplant due to concerns that they will not receive their organs in time and that the possibility of transplantation will compromise appropriate terminal care. 15 Patients listed for lung transplantation are often removed from the transplant waiting list when they enter a terminal phase. 16 In other centers, lung transplantation is routinely practiced for patients with CF reaching respiratory failure and requiring mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Other than B. cepacia, no pretransplantation variables have been shown to affect post-transplantation survival (12,13). We used the U.S. CF Foundation Patient Registry (CFFPR) and the United Network for Organ Sharing (UNOS) database to analyze post-transplantation survivorship to discover additional variables that may help predict success or failure with lung transplantation for patients with end-stage lung disease from CF.…”
mentioning
confidence: 99%
“…It should be noted the predicted life expectancy without transplant for this cohort was approximately 1 year, and more than half the population died without undergoing transplantation. In the third related audit, we demonstrated that our transplant outcomes (survival) were not affected by how severe the child's CF lung disease was at the time of transplant (135). With this audit, it should be noted that we had a policy of not transplanting children who were ventilated, and it has been demonstrated that both adults and children who undergo lung transplantation while receiving invasive ventilation have a poorer outcome than other re-cipients (11).…”
Section: Paul Aurora and Helen Spencermentioning
confidence: 85%
“…National systems can be structured so as to take into account expert clinician judgment, as was demonstrated during this meeting by descriptions of the British and Canadian systems (7,134,135). It may well be the case, as some have argued, that outcomes for transplantation in the United States are determined to a large part by bureaucratic processes rather than variations in surgical or medical procedures.…”
Section: In Spite Of Revisions In National Policies To Manage Lung Trmentioning
confidence: 99%